2021
DOI: 10.21203/rs.3.rs-327980/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Common Host Factors Involved in the Function of the Foot-and-mouth Disease Virus and Classical Swine Fever Virus Internal Ribosomal Entry Sites

Abstract: Foot-and-mouth disease virus (FMDV) and classical swine fever virus (CSFV) both possess positive strand RNA genomes and an internal ribosomal entry site (IRES) element within their 5¢-untranslated regions. To identify common host factors involved with the activity of these IRESes, we utilized cell lines expressing a bicistronic luciferase reporter plasmid, which contained an FMDV-IRES or CSFV-IRES element between the Renilla and firefly luciferase genes. First, we treated FMDV-IRES cells with French maritime p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A recent study has shown that pycnogenol (a compound of natural chemicals from the bark of a fine European tree) was treated for 72 h in the B10 cell line expressing FMDV IRES, which showed a significant decrease in FMDV IRES activity. Additional results showed that 115 host genes were downregulated using pycnogenol, which suggested that the suppression of FMDV IRES activity could be due to the downregulation of host genes ( 131 ). Studies regarding herbal extracts summarized in this review, compared to type I IRES viruses, the herbal extracts that can potentially restrict IRES-dependent translation are negligible in type II IRES viruses, especially those against FMDV.…”
Section: Type II Ires and The Itafs Regulating Its Translationmentioning
confidence: 99%
“…A recent study has shown that pycnogenol (a compound of natural chemicals from the bark of a fine European tree) was treated for 72 h in the B10 cell line expressing FMDV IRES, which showed a significant decrease in FMDV IRES activity. Additional results showed that 115 host genes were downregulated using pycnogenol, which suggested that the suppression of FMDV IRES activity could be due to the downregulation of host genes ( 131 ). Studies regarding herbal extracts summarized in this review, compared to type I IRES viruses, the herbal extracts that can potentially restrict IRES-dependent translation are negligible in type II IRES viruses, especially those against FMDV.…”
Section: Type II Ires and The Itafs Regulating Its Translationmentioning
confidence: 99%